The king of Attolia - Turner, Megan Whalen (New York Greenwillow Books, 2006)
Eugenides, still known as a Thief of Eddis, faces palace intrigue and assassins as he strives to prove himself both to the people of Attolia and to his new bride, their queen
1
LITERATURE, NEW
Keywords: Adventure and adventurers -- Fiction; Kings, queens, rulers, etc -- Fiction; Loyalty -- Fiction; Robbers and outlaws -- Fiction; Soldiers -- Fiction